Affordance alteration in the contexts of video game communities - Laman, Landon Paul, author; Wolfgang, Justin David, advisor; Castillo, Dani, committee member; Marx, Nick, committee member (Colorado State University. Libraries, 2024)
This study analyzes a group of players within the online video game Grand Theft Auto 5 in the context of their relationships to affordances within the game and how they alter these affordances to curate the game to their desires. The group within this study has a rigid social hierarchy and limits their available affordances through the game for a more intimate knowledge of its functions and increased senses of accomplishment through group play. This study utilizes Gibson's affordances to explain the relationship between player and world, social identity theory to examine the group dynamic and its impact on conceptualization of self and group, media system dependency theory to unravel the motivations of the players, and CTDA to analyze the group's utilization of the platform as a place for community gathering and meaning making. This study was conducted through 1:1 interviews with members of the group to understand their interactions, feelings, and motivations behind their restrictive brand of play and the difference between the spirit and the word of the rule set.
Keywords: media communication; affordance alteration; video game communities